SIMA KUMARI - SIMA KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
It is absolutely necessary to have a solid understanding of the nature of the changes that occur in rural landscapes as a result of the process of urbanization in order to establish rural management plans for sustainable development. These plans must take into account the effects that urbanization has on rural areas. Regrettably, there is a dearth of research on how changes occur in rural environments, and there is no evidence as to how these changes may be altered for the better. In addition, there is a lack of knowledge on how rural communities can adapt to these changes. There were 244.9 million households in India, 179.7 million of which were situated in rural areas, which accounted for 833 million of the country's total population. India's overall population was 1.25 billion (SECC Survey 2011). According to the findings of a study, 87.20 million rural households had at least one member who satisfied the criterion for deprivation, while 92 million rural households had at least one member who participated in agricultural or manual labour activities on an occasional basis. There is no debate about the significant role that women play in the agriculture sector. They are active in related businesses as well, such as cattle management, dairying, beekeeping, goat rearing, mushroom cultivation, and poultry farming, amongst others, and contribute to every part of agricultural operations via their involvement. It was projected that 27.44% of women participated in the workforce in 2011, while 72.56% of men did so.